PENINGKATAN KESADARAN LINGKUNGAN MASYARAKAT PUGER: WASTE CHANGE MENDUKUNG KONSEP HIJAU 3R (REDUCE-REUSE-RECYCLE) - Novikarumsari, Nurul Dwi; Anggraeni, Rosmayniar; Rokhani; Sofia (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2024)
The majority of community in Puger Village work as fishermen and they live near the coast. The problems faced by the community on a daily basis include the lack of awareness about environmental cleanliness and how they dispose of and utilize domestic and productive waste. The Joint Business Group (KUB), as one of the institutional forms in Puger, shows that there are still few activities within the group that focus on environmental maintenance, which can support the productive activities of fishermen. This community service activity includes: 1) increasing environmental awareness and 2) waste management by KUB Gotong Royong to enhance the capacity of the previously inactive group. The methods in this service include: socialization to strengthen the group, environmental awareness counseling, assistance in waste management (organic and inorganic), and management towards 3R (reuse, reduce, and recycle). The results achieved from this activity are that the people of Puger Village, especially members of KUB Gotong Royong, are able to increase their awareness to implement the separation of organic and inorganic waste in accordance with the application of the green concept of 3R (Reuse, Reduce, and Recycle). By implementing this community service activity, the people of Puger Village can better maintain the cleanliness of the surrounding environment.